Operation Feasibility Study of the Prafi Substation and 150 kV Manokwari-Prafi Transmission Line Project - Ova Kurniawan; Zulkifli Palinrung; Ferry Budhi Susetyo (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2025)
The rising demand for electricity in Manokwari, the capital of West Papua Province, Indonesia, necessitates urgent improvements to the existing 20 kV distribution system, which struggles to maintain voltage compliance with grid code standards and meet projected future loads. This study examines two operational alternatives: (1) the construction of a 150 kV transmission line from the Gas Engine Power Plant (PLTMG) substation to the Prafi Substation, and (2) the development of an express feeder from the same source. Using DigSILENT PowerFactory software, operational feasibility is assessed through voltage regulation, transformer and line loading analysis, and N-1 contingency compliance. The investigation includes power flow simulations, short-circuit fault analysis, and system stability evaluations, focusing on rotor angle, voltage, and frequency stability. Findings provide technical recommendations to enhance the reliability, resilience, and sustainability of Manokwari’s power infrastructure, supporting strategic planning and operational optimization.